Morfologia e propriedades mecânicas da fibra de sisal unidirecional e em sobreposição de compósito com resina epóxi - Holanda, Elisângela Bezerra das Neves (2013)
The composites manufactured with long fibres aligned in a single direction, and overlay has been shown to have better performance than the short fibers randomly distributed. In particular, the lignocellulosic fibers extracted from the sisal leaves, used in conjunction with the epoxy resin has attracted the attention of many researchers because the final properties of the system formed. In this work composites based on epoxy resin reinforced with sisal fibers were manufactured. The sisal fibres were treated with an alkaline solution of 0.06 mol/l NaOH. The treated, and untreated fibres were subjected to tension x extension tests. The composites were manufactured in the "Lossy" mold with the specifications of the samples to be produced (300x20x4 mm). The tension tests were carried out in accordance with the ASTM standards 3039 (for the composite aligned in a single direction) and ASTM D5573 (for composites in overlay), three point bending tests were performed according to ASTM D790. Analyzing the results of the tests of tension and three point bending tests, it was observed that the composites with the configuration of overlapping had the better elastic module in both tests. As to the maximum resistance to tension, the best result was the composites aligned in a single direction. Tests of absorption of water and micrographs are in progress